Blood Parameters and Length of Hospitalization in Pediatric Dengue Virus Infection Patients - Salsabiela, Salwa; Puspitasari, Metana; Jatmiko, Safari Wahyu (Universitas Muhammadiyah Surakarta, 2024)
This research aims to evaluate the correlation between erythrocyte level, hematocrit, hemoglobin, and Hb/RDW ratio with the length of hospitalization in pediatric patients with DVI. This observational study used a cross-sectional design and analyzed secondary data from 41 pediatric DVI patients at PKU Muhammadiyah Sampangan Surakarta Hospital. The correlation between hematological parameters and length of hospitalization was analyzed using the Spearman test. Laboratory results showed a mean erythrocyte count of 5.05 million cells/nL (SD 0.61), a median hematocrit of 39.5%, hemoglobin of 13.6 g/dL, and Hb/RDW ratio of 1.03. Bivariate correlation test showed erythrocyte level (r = 0.027, p = 0.867), hematocrit (r = -0.004, p = 0.983), hemoglobin (r = 0.079, p = 0.625), and Hb/RDW ratio (r = 0.116, p = 0.472) showed no significant association with length of hospitalization. This study provides insights into the relationship between hematological parameters and the length of hospital stay in pediatric dengue patients. While no significant correlation was found, it highlights the complexity of factors influencing outcomes and the need to explore other prognostic markers. Conducted in an Indonesian endemic region, the research contributes to understanding DVI management and underscores the importance of a comprehensive, multifactorial approach to improving patient care strategies.